Perancangan Sistem Informasi Pendaftaran Peserta Didik Baru Berbasis Web pada SMK Kosgoro Kota Bogor - Dicky Maulana; Indah Suryani (Indonesian Journal on Software Engineering (IJSE), 2019)
Abstract: New Student Admission is one process that exists in educational institutions such as schools that are useful for screening prospective students who are selected according to the criteria determined by the school to become students. In general, the process of admitting new students is done through the stages of registration, selection tests and announcements of new student admissions. So far, Kosgoro Vocational School has registered new student participants in a manual and not computerized way, causing time constraints and more costs for prospective students. In developing this application using the waterfall method includes the stages of determining software requirements, program design and testing of applications that have been made, In terms of making this website using Codeigniter and PHP so that the web display is more attractive and more efficient in accepting new students and providing convenience to prospective students to be able to register online and administrative staff can use it and see the latest developments in new student registration. Keywords: New student registration, website, registration system